APLIKASI ABSENSI KARYAWAN BERBASIS ANDROID MENGGUNAKAN CODE QR DAN GEOFENCE (STUDI KASUS PT INDOSALUYU PRIMAJAYA) - Noviyanti Fazriyah; Redi Darmawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Attendance data is included in the formative value, at this time PT.Indosaluyu Primajaya still uses a manual system, this system has the potential to cause problems in the form of data present on paper that does not match the number of employees present in the office. The solution is to design absences using QR Code and geofence on Android as security when taking absences, in order to prevent students outside the PT.Indosaluyu Primajaya area from filling in absences. From the results of this system design, it produces a paperless system and prevents manipulation of absent data.